Sistem Informasi Pendataan dan Pengajuan Peralatan Ekstrakurikuler Berbasis Web Studi Kasus SD Bosowa Bina Insani - Hakim, Mochammad Fauzan; Kusumah, Fitrah Satrya Fajar; Rachmawati, Fitria (Universitas Batanghari Jambi, 2025)
The purpose of this research is to develop a web-based system for equipment data collection and submission at SD Bosowa Bina Insani, enabling systematic data management and addressing the existing issues. The system development was conducted using the waterfall method. The waterfall method is a structured framework for taking action or organizing ideas in a directed manner to achieve specific goals. The result of this research is the creation of an information system for item data collection and submission that operates systematically.